Solid state gas sensor. (2022) - Naz, Shaheen; Javid, Iqra; Konwar, Subhrajit; Singh, Pramod K.; Sahni, Mohit; Bhattacharya, Bhaskar
Abstract: With the high competition in market, the increase in quality and reliability of gas sensors is highly desirable. Compatible gas sensors having high precision, high sensitivity, economical have attracted a lot of attention. For good gas sensing, research on sensing material have been broadly focused. An improvement in Nano technology and use of different materials has led to the development of efficient and effective gas sensors. The Nano- materials manifest properties that are incomparable with the granular polycrystalline counterpart. With the advancement in Micro and Nano technology, micro-sized gas sensors have been developed with great sensing performance. For detection of toxic gases various techniques are available but solid state gas sensors offer a wide spectrum of materials and their sensitivities towards various types of gases. Of all the solid state gas sensing materials, semiconductor metal oxide nanostructures are more preferable due to the stability of their oxides, high response, low cost for fabrication, response to wide range of chemicals etc. They are cost effective, reliable, and robust and have quick response time. In this paper we have studied about the semiconductor metal oxide gas sensors. The effects due to morphological structure on sensing properties are also discussed. The existing detailed literature survey on techniques and mechanisms for the nanostructures and their gas sensing ability are also involved.